Conditional U1 Gene Silencing in Toxoplasma gondii. - Manuela S Pieperhoff; Gurman S Pall; Elena Jiménez-Ruiz; Sujaan Das; Carmen Melatti; Matthew Gow; Eleanor H Wong; Joanne Heng; Sylke Müller; Michael J Blackman; Markus Meissner (PLoS ONE)
The functional characterisation of essential genes in apicomplexan parasites, such as Toxoplasma gondii or Plasmodium falciparum, relies on conditional mutagenesis systems. Here we present a novel strategy based on U1 snRNP-mediated gene silencing. U1 snRNP is critical in pre-mRNA splicing by defining the exon-intron boundaries. When a U1 recognition site is placed into the 3'-terminal exon or adjacent to the termination codon, pre-mRNA is cleaved at the 3'-end and degraded, leading to an efficient knockdown of the gene of interest (GOI). Here we describe a simple method that combines endogenous tagging with DiCre-mediated positioning of U1 recognition sites adjacent to the termination codon of the GOI which leads to a conditional knockdown of the GOI upon rapamycin-induction. Specific knockdown mutants of the reporter gene GFP and several endogenous genes of T. gondii including the clathrin heavy chain gene 1 (chc1), the vacuolar protein sorting gene 26 (vps26), and the dynamin-related protein C gene (drpC) were silenced using this approach and demonstrate the potential of this technology. We also discuss advantages and disadvantages of this method in comparison to other technologies in more detail.